Comparison of performance between MARKOWITZ model and enhanced index tracking model - Loh, Jia Yi; Siti Norafidah Mohd Ramli; Noriza Majid (Penerbit Universiti Kebangsaan Malaysia, 2020)
The rapid growth of exchange-traded fund (ETF) in Malaysia and recommendation of investment professionals raise doubt on whether a portfolio which tracks the performance of an index will perform better than a carefully built portfolio, such as the one built by using the classical Markowitz Model. Thus, the composition of an optimal portfolio built based on the Markowitz model and enhanced index tracking model using the data of finance, plantation and industrial indices of the Malaysian stock market from 2012-2017 will be investigated. Comparisons are made on their risk-adjusted performance using expected return, the Sharpe ratio and information ratio. The study found that the Markowitz portfolio includes only 31.43% to 33.33% of the respective index components inside the portfolio built. Overall, the Markowitz model outperforms the enhanced index tracking model in constructing an optimal portfolio with a higher expected return, Sharpe ratio and information ratio in finance and industrial sectors.